Pumpkin cellulose is a prospective additive for providing bread with healthy properties - Shevchenko, Anastasiia (My University, 2022)
Pumpkin cellulose is a promising raw material for inclusion in the recipe of bakery products based on wheat flour due to the high content of dietary fibers and the possibility of providing the body with a significant amount of this nutrient. In addition, such products are able to normalize the course of physiological processes in the body in modern adverse environmental conditions, neuroemotional and physical overloads.
Keywords: pumpkin cellulose; dough; bakery product; fiber; integral rate; кафедра технології хлібопекарських і кондитерських виробів